Serum S100 calcium-binding protein P in systemic lupus erythematosus patients with lupus nephritis and thrombotic microangiopathy: a 12-month longitudinal biomarker study - Rasmia Elgohary; Ahmed Fayed; Mohamed Abdelkader Morad; Karem Mohamed Salem; Gehad Maghraby (The Egyptian Journal of Internal Medicine, 2026)
Abstract Purpose Lupus nephritis (LN) complicated by thrombotic microangiopathy (TMA) represents a severe renal phenotype characterized by immune-mediated inflammation and microvascular injury. S100 calcium-binding protein P (S100P) participates in inflammatory and stress-related signaling, providing a biological rationale for evaluating its potential as a circulating biomarker in LN-TMA. Methods In this single-center longitudinal biomarker study nested within an observational cohort, 100 patients with systemic lupus erythematosus (SLE) and biopsy-confirmed proliferative LN (ISN/RPS class III or IV) with concomitant TMA were evaluated together with 50 age- and sex-matched healthy participants included for baseline biomarker comparison. Serum S100P was measured at baseline and at 6 and 12 months, and longitudinal changes were examined in relation to renal response, conventional laboratory parameters, SLEDAI-2 K, and renal histopathological indices. Results Baseline serum S100P was markedly higher in patients with LN-TMA than in healthy participants [median 21.3 (IQR 19.1–24.0) versus 0.1 (0.1–1.0) ng/mL; P < 0.001]. Baseline S100P was not significantly associated with SLEDAI-2 K or renal biopsy activity and chronicity indices. At 6 months, partial responders had lower S100P concentrations than nonresponders [8.5 (7.6–9.2) versus 12.4 (8.6–23.2) ng/mL; P = 0.004; AUC = 0.811]. At 12 months, complete responders had substantially lower concentrations than nonresponders [7.5 (6.7–8.4) versus 27.3 (24.3–29.3) ng/mL; P < 0.001; AUC = 0.967]. Longitudinal S100P changes were associated with changes in creatinine, lactate dehydrogenase, C3, and C4. Conclusion In this single-center LN-TMA cohort, serum S100P was markedly elevated compared with healthy participants and declined substantially among patients achieving renal response. These findings support an association between longitudinal S100P changes and treatment response but do not establish disease specificity or pretreatment predictive value. S100P should therefore be considered a candidate complementary monitoring biomarker requiring validation in larger multicenter cohorts with appropriate disease-control groups.